A Case of Multiple Myeloma Coexisting with Primary Hyperparathyroidism and Review of the Literature - Nasir Hussain; Moona Khan; Aparna Natarajan; Mubeenkhan Mohammedabdul; Usman Mustafa; Kalpana Yedulla; Aibek E. Mirrakhimov (Case Reports in Oncological Medicine)
Hypercalcemia is a common medical problem with an estimated prevalence of 15% among hospitalized patients. Multiple myeloma (MM) and primary hyperparathyroidism (PHPT) are among the most common causes of hypercalcemia but coexistence of both pathologic processes in a patient is an extremely rare phenomenon. In this paper we have discussed a patient presenting with this rare phenomenon. We have also provided a comprehensive review of the scientific literature published on codiagnosis of MM and PHPT.